FAKTOR YANG BERHUBUNGAN DENGAN STRESS KERJA PADA PERAWAT DI BLUD RS KONAWE SULAWESI TENGGARA TAHUN 2020 - Eny Suarni; Sartiah Yusran; Syawal Kamiluddin Saptaputra (FKM Universitas Halu Oleo, 2021)
Work stress is a form of psychological response of the body to the pressures and demands of work that exceed the limits of one's abilities, which are physical or environmental demands as well as in social interactions. The purpose of this study was to find out the relationship between workload, shift, salary, and interpersonal relationship with work stress on nurses at BLUD RS Konawe Southeast Sulawesi. This study was an analytical study with a cross sectional study approach. The variables ini this study included work stress, workload, work shift, salary, and interpersonal relationships. The population was all nurses who work in BLUD RS Konawe numbered 164 people. The sample of this study was 115 people who were obtained by the simple random sampling technique method. The results of this study indicate that there is a statistically significant relationship (Pvalue<0.05) between workload variables with work stress (Pvalue=0.000) and shift variables with work stress (Pvalue=0.014). There is no statistical relationship (Pvalue>0.05) variable relationship of salary with work stress (Pvalue=0.875) because the salary is already satisfactory. Then the interpersonal relationship with work stress (Pvalue=0.836) on nurses is not related because interaction and communication goes well. The conclusion in this study is that there is a relationship between workload and work shift with work stress and there is no relationship between salary and interpersonal relationship with work stress on nurses at BLUD RS Konawe